The role of grammatical role and thematic role predictability in reference form production in Mandarin Chinese - Hwang, Heeju; Lam, Suet Ying; Ni, Wenjing; Ren, He (Frontiers in Psychology, 2022)
Evidence suggests that English speakers use pronouns when referring to the grammatical subject and predictable thematic role. We tested how grammatical role and thematic role predictability affect different types of referential forms, namely, overt pronouns and null pronouns in Mandarin Chinese. We found that both overt and null pronouns were sensitive to grammatical role. However, we did not find any evidence that overt and null pronouns were sensitive to thematic role predictability. Although null pronouns were influenced by grammatical role, the rate of null pronouns for subject reference was very low compared to that of overt pronouns. Given frequent occurrence of null pronouns in Mandarin, our results suggest that the use of null pronouns may not be explained by a simple grammatical role mechanism.